KEANEKARAGAMAN JENIS LUMUT (BRYOPHYTA) PADA BERBAGAI SUBSTRAT DI BUKIT MUNTAI KABUPATEN BANGKA SELATAN - Mirza Fanani; Budi Afriyansyah; Ida Haerida (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2019)
Muntai hill is one of the potential sector for bryophyte diversity habitats. Muntai Hill was in regular part of Lubuk Besar Muntai Palas of production forest sector that has a 400 ha and height 265 mdpl of area at South Bangka Region. This research aimed to assessed variant of Bryophyte diversity at Muntai Hill. The data is collected that used exploration method. Bryophyte that found during exploration is collected, made the herbarium and the last is identificated. Result of research showed there are 20 Bryophyte variants consist of 16 types of mosses (8 Families), and 4 types of liverworts (4 families). Calymperaceae and Sematophyllaceae are most commont types mosses family that have found while liverworts of each family only found 1 type. The bryophyte lived in Muntai Hill can be found on the stone, trunk, rotten wood and ground substrats. The stone is the most overgrown substrat by Bryophyte that is 62%.